Experience with clinical cerebral autoregulation testing in children hospitalized with traumatic brain injury: Translating research to bedside - Kunapaisal, Thitikan; Moore, Anne; Theard, Marie A.; King, Mary A.; Chesnut, Randall M.; Vavilala, Monica S.; Lele, Abhijit V. (Frontiers in Pediatrics, 2023)
Objective: To report our institutional experience with implementing a clinical cerebral autoregulation testing order set with protocol in children hospitalized with traumatic brain injury (TBI). Methods: After IRB approval, we examined clinical use, patient characteristics, feasibility, and safety of cerebral autoregulation testing in children aged <18 years between 2014 and 2021. A clinical order set with a protocol for cerebral autoregulation testing was introduced in 2018. Results: 25 (24 severe TBI and 1 mild TBI) children, median age 13 years [IQR 4.5; 15] and median admission GCS 3[IQR 3; 3.5]) underwent 61 cerebral autoregulation tests during the first 16 days after admission [IQR1.5; 7; range 0-16]. Testing was more common after implementation of the order set (n=16, 64% after the order set vs. n=9, 36% before the order set) and initiated during the first two days. During testing, patients were mechanically ventilated (n=60, 98.4%), had invasive arterial blood pressure monitoring (n=60, 98.4%), had intracranial pressure monitoring (n=56, 90.3%), brain-tissue oxygenation monitoring (n=56, 90.3%), and external ventricular drain (n=13, 25.5%). Most patients received sedation and analgesia for intracranial pressure control (n=52; 83.8%) and vasoactive support (n=55, 90.2%) during testing. Cerebral autoregulation testing was completed in 82% (n=50 tests); 11 tests were not completed (high intracranial pressure [n=5], high blood pressure [n=2], bradycardia [n=2], low cerebral perfusion pressure [n=1], or intolerance to blood pressure cuff inflation [n=1]). Impaired cerebral autoregulation on first assessment resulted in repeat testing (80% impaired vs. 23% intact, RR 2.93, 95% CI 1.06:8.08, p = 0.03). Seven out of 50 tests (14%) resulted in a change in cerebral hemodynamic targets. Conclusions: Findings from this series of children with TBI indicate that: 1) Availability of clinical order set with protocol facilitated clinical cerebral autoregulation testing, 2) Clinicians ordered cerebral autoregulation tests in children with severe TBI receiving high therapeutic intensity and repeatedly with impaired status on the first test, 3) Clinical cerebral autoregulation testing is feasible and safe, and 4) Testing results led to change in hemodynamic targets in some patients.